Clostridioides difficile Enteritis in Patients Following Total Colectomy—a Rare but Genuine Clinical Entity. (31st October 2019) - Ulrich, Robert J; Bott, Jonathan; Imlay, Hannah; Lopez, Kerri; Cinti, Sandro; Rao, Krishna
Abstract : Clostridioides difficile enteritis (CDE) after colectomy is an understudied infectious syndrome. We reviewed 20 years of post-colectomy data and found CDE in 44/855 (5.1%) patients, usually within one year of surgery. Risk factors include acid suppression, inflammatory bowel disease, and antibiotics with enteral feeds. Clostridioides difficile enteritis often presents with severe disease requiring hospitalization. Abstract: Objective: Clostridioides difficile infection (CDI) frequently causes colitis following antibiotic exposure and is a leading cause of gastrointestinal infectious mortality. Infection in the small bowel, C. difficile enteritis (CDE), was previously thought impossible, but case series have challenged this dogma. Clostridioides difficile enteritis prevalence, severity, and potential risk factors are unknown. Methods: We retrospectively analyzed all total colectomy patients over a 20-year period at our institution. C. difficile enteritis was defined by clinical symptoms and positive C. difficile stool testing after colectomy. We compared CDE cases to controls using multivariable analysis to identify potential CDE risk factors. Results: C. difficile enteritis occurred in 44 of 855 (5.1%) patients, a median of 130 days after colectomy. Compared to controls, CDE patients were similar in age, gender, and presence of immunosuppression. The majority (64%) had antibiotics <30 days prior to CDE. In multivariable analysis, CDE risk factors included perioperative acid suppression (hazard ratio [HR], 2.52; 95% confidence interval [CI], 1.26–5.04; P = .009), colectomy for inflammatory bowel disease (HR, 2.95; CI, 1.29–6.72; P = .010), colectomy for CDI (HR, 9.95; CI, 2.70–36.63; P ≤ .001), and β-lactam use in the setting of enteral feeds (HR, 17.83; CI, 2.75–115.68; P = .003). C. difficile enteritis presented with severe disease half of the time, with 81.8% requiring hospitalization. Conclusions: C. difficile enteritis is a rare clinical entity that should be considered in postcolectomy patients presenting with CDI symptoms, even years after surgery. Like traditional CDI, likely CDE risk factors include acid suppression and inflammatory bowel disease. Prior antibiotic use in the setting of enteral feeds may amplify CDE risk. C. difficile enteritis often presents as severe disease and frequently requires hospitalization.